Generation of 2 µm Laguerre–Gaussian mode in a Tm:LuYAG solid-state laser. (27th February 2018) - Liu, Qiyao; Ding, Manman; Zhao, Yongguang; Zhou, Wei; Shen, Deyuan
Abstract: In this article, we discuss the first vortex laser in the 2 µ m spectral range directly generated from a Tm:LuYAG oscillator, in which a pump beam with annular intensity distribution is employed in line with Laguerre–Gaussian modes. Laser thresholds of different-order Laguerre–Gaussian modes are theoretically analyzed and discussed. Vortex lasers with orbital angular momentum of ħ and  − ħ were experimentally produced with corresponding output powers of 1.75 W and 1.64 W, respectively. This directly emitted vortex laser generated in the ~2 µ m region from a compact and robust Tm:LuYAG oscillator has potential applications in the areas of molecular spectroscopy and organic material processing amongst others.